2018
DOI: 10.1111/cdev.13113
|View full text |Cite
|
Sign up to set email alerts
|

Three‐ to Four‐Year‐Old Children Rapidly Adapt Their Predictions and Use Them to Learn Novel Word Meanings

Abstract: Adults create and update predictions about what speakers will say next. This study asks whether prediction can drive language acquisition, by testing whether 3- to 4-year-old children (n = 45) adapt to recent information when learning novel words. The study used a syntactic context which can precede both nouns and verbs to manipulate children's predictions about what syntactic category will follow. Children for whom the syntactic context predicted verbs were more likely to infer that a novel word appearing in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
72
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 36 publications
12
72
3
Order By: Relevance
“…This perspective receives support from numerous studies showing that prediction effects during language comprehension are absent or less pronounced for populations with reduced executive resources, such as children, older individuals, and non-native speakers (e.g., Federmeier et al, 2002;Federmeier & Kutas, 2005;Dagerman, et al, 2006;Federmeier et al, 2010;Mani & Huettig, 2012;Wlotko & Federmeier, 2012;Martin et al, 2013;Kaan, 2014;Mitsugi & Macwhinney, 2016;Gambi et al, 2018;Payne & Federmeier, 2018;cf. Dave et al, 2018;Havron et al, 2019). Furthermore, several neuroimaging studies have reported sensitivity to linguistic manipulations in what appear to be cortical regions thought to support domain-general executive function (e.g., Kaan & Swaab;Kuperberg et al, 2003;Novick et al, 2005;Rodd et al, 2005;Novais-Santos, 2007;January et al, 2009;Peelle et al, 2010;Rogalsky & Hickock, 2011;Nieuwland et al, 2012;Wild et al, 2012;McMillan et al, 2012McMillan et al, , 2013, suggesting that such regions may also be implicated in language processing, including perhaps prediction.…”
Section: Introductionmentioning
confidence: 99%
“…This perspective receives support from numerous studies showing that prediction effects during language comprehension are absent or less pronounced for populations with reduced executive resources, such as children, older individuals, and non-native speakers (e.g., Federmeier et al, 2002;Federmeier & Kutas, 2005;Dagerman, et al, 2006;Federmeier et al, 2010;Mani & Huettig, 2012;Wlotko & Federmeier, 2012;Martin et al, 2013;Kaan, 2014;Mitsugi & Macwhinney, 2016;Gambi et al, 2018;Payne & Federmeier, 2018;cf. Dave et al, 2018;Havron et al, 2019). Furthermore, several neuroimaging studies have reported sensitivity to linguistic manipulations in what appear to be cortical regions thought to support domain-general executive function (e.g., Kaan & Swaab;Kuperberg et al, 2003;Novick et al, 2005;Rodd et al, 2005;Novais-Santos, 2007;January et al, 2009;Peelle et al, 2010;Rogalsky & Hickock, 2011;Nieuwland et al, 2012;Wild et al, 2012;McMillan et al, 2012McMillan et al, , 2013, suggesting that such regions may also be implicated in language processing, including perhaps prediction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a recent study, familiar words were used to induce children to expect either a noun or a verb following a specific syntactic context (that could be followed by either nouns or verbs). Thus, after hearing four familiar verbs in this context, children were more likely to infer that a novel word appearing in this context referred to an action, than children who heard four familiar nouns in this context (Havron, de Carvalho, Fiévet, & Christophe, 2019).…”
Section: Introductionmentioning
confidence: 89%
“…Appendix for the items), because no distractor is available. No feedback is given to the participants to validate their interpretation after their choice, in any item, induction or test, as was the case in other similar previous studies(Havron et al, 2019;Yurovsky et al, 2016 andDautriche et al, 2018).…”
mentioning
confidence: 99%
“…First, researchers might choose to perform the analysis over the duration of the whole trial (orange line in Figure 3, panel a; panel c). Alternatively, they might choose an analysis such as the nonparametric permutation test (Maris & Oostenveldt, 2007; see Havron, de Carvalho, Fiévet, & Christophe, 2019, for an implementation in a visual world task with young children), which will determine the time windows of statistically significant differences in a bottom‐up fashion without inflating false‐positive rates (the time window in which the permutation analysis shows a significant effect is illustrated by the red shaded area in Figure 3, panel a). These choices have the advantage of not being tied to any specific predetermined time window.…”
Section: Best Practices In Preregistration For Infant Studiesmentioning
confidence: 99%